The influence of the use of mobile devices and the cloud computing in organizations. - Moreira, Fernando (2015)
In the last decade, companies tend to become virtualized. This virtualization is due in large part to developments in the use of mobile platforms and the impact on their infrastructure. The concept of BYOD (Bring Your Own Device) adoption and use of cloud computing are having profound implications for how the technologies are being used, as well as the interaction between individuals and these technologies. In this context, we conducted a study based on a questionnaire about the impact of the use of mobile devices and the cloud in organizations, taking into consideration their use in performing professional and personal tasks. With the questionnaire and its subsequent analysis it was found that organizations have a lack of understanding about almost all of the implications and consequences of the use of mobile devices and the cloud.